Penalties for Unregistered Marriage and Polygamy in Indonesia, Pakistan and Tunisia - Fidiani, Faida (Sakina: Journal of Family Studies, 2021)
Indonesia, Pakistan and Tunisia are countries with a majority Muslim population. These three countries have different regulations regarding unregistered marriages and sanctions for violating these regulations. In order to know the regulations and sanctions between the three countries, a comparison was made between Indonesia, Pakistan and Tunisia. So, aims of this research is analyze about comparison and implementation of penalties in Indonesia, Pakistan and Tunisia. This research is a type of normative research or library research and use comparative approach. The results of this research are penalty in Indonesia is a fine if does not inform the will of marriage to the PPN and for polygamy is allowed for certain reasons and certain conditions. In Pakistan fines or imprisonment or both if the marriage is not done in front of a registrar and do polygamy without wife’s approval and ask the Arbitration Council for permission. In Tunisia the penalty of imprisonment applied if marriage without 2 witnesses or 2 witnesses and a registrar, and if do polygamy will be subject to penalties in the form of fine and imprisonment.